Comprehensive analyses of telomerase component DKC1 and its association with clinical, molecular and immune landscapes in uterine corpus endometrial carcinoma - Sun, Chenxi; Liu, Xu; Liu, Tiantian; Fan, Chenliu; Jiang, Yang; Li, Binggen; Yuan, Huiyang; Zheng, Chengyun; Xu, Dawei (Frontiers in Cell and Developmental Biology, 2025)
BackgroundTelomerase activation is essential to malignant transformation and progression including uterine corpus endometrial carcinoma (UCEC), while telomerase co-factor DKC1-mediated RNA pseudouridylation is required for functional telomerase by stabilizing telomerase RNA component (TERC) and its upregulation occurs in many cancers. Surprisingly, there is only one publication studying DKC1 in UCEC, which shows its significant downregulation.ObjectiveDKC1 expression, its role in the UCEC molecular pathogenesis and clinical implications were comprehensively investigated.MethodsThirty UCEC patients were recruited to determine DKC1 expression in both tumors and non-tumorous endometrial tissues (NT) using immunohistochemistry. Four UCEC cohorts from TCGA and GSE datasets were analyzed for DKC1 expression and its impacts on clinic-pathological, molecular, genomic and immune landscapes.ResultsImmunohistochemistry analyses showed significantly increased DKC1 expression in UCEC tumors than in NTs and its highest level was observed in high-grade tumors. For the TCGA cohort, DKC1 mRNA and protein levels increased significantly in tumors compared with that in NTs. DKC1 mRNA levels positively correlated with TERC and telomerase activity. Higher DKC1 expression predicted shorter patient overall and progression-free survival. DKC1 copy number alterations were frequent in UCEC tumors. Estrogen treatment of UCEC cells upregulated DKC1 expression while medroxyprogesterone inhibited its expression. DKC1-high UCEC tumors exhibited hyperproliferation, increased stemness and epithelial-mesenchymal transition, accompanied by significantly higher aneuploid, homologous recombination deficiency and micro-satellite instable scores, and higher frequencies of cancer driver aberrations. Lower immune scores were observed in DKC1-high tumors as assessed by ESTIMATE algorithm. Tumor Immune Dysfunction and Exclusion (TIDE) analyses revealed robustly higher TIDE scores featured with T Cell exclusion in DKC1-high tumors, and consistently, the diminished trafficking of immune cells into tumor tissues and substantial declines in immune cell infiltration were shown in these tumors. Moreover, DKC1-high tumors exhibited poor response to immune checkpoint inhibitor (ICI)-based immunotherapy. These observations were validated by the findings obtained from other datasets.ConclusionThe present findings unravel genomic alteration- and sex hormone-mediated dysregulation of the telomerase cofactor DKC1 in UCEC tumors, and its upregulation participates actively in the UCEC pathogenesis through tumor-intrinsic and extrinsic mechanisms. DKC1 assessment is useful for patient prognostication and personalized interventions.